A practical guide to interpreting germline variants that drive hematopoietic malignancies, bone marrow failure, and chronic cytopenias - Feurstein, Simone; Hahn, Christopher N.; Mehta, Nikita; Godley, Lucy A. (Genetics in medicine, 2022)
Purpose - The American College of Medical Genetics and Genomics and the Association for Molecular Pathology guidelines for germline variant interpretation are implemented as a broad framework by standardizing variant interpretation. These rules were designed to be specified, but this process has not been performed for most of the 200 genes associated with inherited hematopoietic malignancies, bone marrow failure, and cytopenias. Because guidelines on how to perform these gene specifications are lacking, variant interpretation is less reliable and reproducible. - Methods - We have used a variety of methods such as calculations of minor allele frequencies, quasi-case-control studies to establish thresholds, proband counting, and plotting of receiver operating characteristic curves to compare different in silico prediction tools to design recommendations for variant interpretation. - Results - We herein provide practical recommendations for the creation of thresholds for minor allele frequencies, in silico predictions, counting of probands, identification of functional domains with minimal benign variation, use of constraint Z-scores and functional evidence, prediction of nonsense-mediated decay, and assessment of phenotype specificity. - Conclusion - These guidelines can be used by anyone interpreting variants associated with inherited hematopoietic malignancies, bone marrow failure, and cytopenias to develop criteria for reliable, accurate, and reproducible germline variant interpretation.